Simultaneous niche expansion and contraction in plant–pollinator networks under drought. Issue 11 (26th August 2022) - Morozumi, Connor; Loy, Xingwen; Reynolds, Victoria; Schiffer, Annie; Morrison, Beth; Savage, Jade; Brosi, Berry
Abstract : Global climate change threatens to substantially rearrange species interactions, yet we lack clear predictions on how these changes will cascade through communities. Many perturbations associated with climate change, such as droughts, will change resource levels, with consequences for species interactions and thus ecological network structure. Diet theory predicts foraging niche expansion when preferred resources are scarce, yet under severe resource reduction interspecific competition could alternatively increase niche partitioning. Such niche expansion and/or contraction could profoundly shape ecological network structure following perturbations, but whether these predictions hold at the community level is unclear. We studied the impacts of drought on plant–pollinator networks in long‐lived perennial plant communities in which drought affects flower and floral reward production. We assessed whether drought effects on available floral resources altered pollinator dietary niche breadth to drive higher network‐level generalization. Accounting for interaction abundance and species turnover, we compared plant–pollinator networks in two drought years and three non‐drought years. We found that drought restructured plant–pollinator networks, resulting in more generalization in terms of presence–absence of links, yet more specialization when accounting for quantitative network intensities. Our results support the application of diet theory to understanding how perturbations may impact ecological network structure.